2015
DOI: 10.1159/000439022
|View full text |Cite
|
Sign up to set email alerts
|

PR Prolongation and Cardiac <sup>123</sup>I-MIBG Uptake Reduction in Parkinson's Disease

Abstract: Background: Cardiac 123I-metaiodobenzylguanidine scintigraphy (MIBG) previously demonstrated an uptake reduction in patients with Parkinson's disease (PD). However, epidemiologic research showed that electrocardiography (ECG) abnormalities occurred prior to motor signs in PD. Here we investigated whether the electrical conduction system of the heart was impaired in PD. Methods: Clinical features, ECG and MIBG parameters were analyzed in 191 patients with PD, 42 with multiple system atrophy (MSA) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…In addition, the present study was consistent with the scholars' reports. 9 In the present study, it was found that the QT interval was positively correlated with the disease course and Hoehn-Yahr classification. The QT interval represents the total time course of ventricular depolarization and repolarization.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In addition, the present study was consistent with the scholars' reports. 9 In the present study, it was found that the QT interval was positively correlated with the disease course and Hoehn-Yahr classification. The QT interval represents the total time course of ventricular depolarization and repolarization.…”
Section: Discussionsupporting
confidence: 55%
“…Foreign scholars have studied 191 patients with PD and found that results of MIBG scintigraphy in 19 PR patients were abnormal. 9 Meanwhile, in the present study, it was found that PR is correlated to the Hoehn-Yahr classification. It was further speculated that the prolongation of PR could be used as a biomarker for autonomic nerve dysfunction in PD.…”
Section: Discussionsupporting
confidence: 49%
“…In our previous studies of patients with PD, the PR interval was correlated with autonomic dysfunction, and autonomic dysfunction was associated with BMI increase. 2,3 The results of the current study indicated a positive correlation between BMI and the PR and QRS intervals. In a large-scale study of normal subjects, prolongation of both the PR and QRS intervals were reported in obese people.…”
Section: Discussionsupporting
confidence: 55%
“…1 Recently, prolongation of the PR interval on electrocardiogram (ECG) was reported to reflect the abnormal MIBG findings in PD. 2 In addition, an increased body mass index (BMI) was associated with autonomic dysfunction in PD as determined using the MIBG method. 3 In this study, we investigated the relation between clinical features, including BMI, and ECG parameters in patients with PD.…”
Section: Introductionmentioning
confidence: 99%
“…1,6 Patients with PD may be predisposed to a prolonged QT interval and are at risk of developing other cardiac abnormalities compared with healthy aged-matched individuals. 7,8 The tendency towards a prolonged QT interval in some patients is likely attributable to autonomic cardiac dysfunction resulting from neuronal degeneration. 9 Risk factors include advanced PD and confounding medications used in PD management, such as domperidone, amantadine, and antidepressants including citalopram and amitriptyline.…”
mentioning
confidence: 99%